A Multi-Period Decision Making Procedure Based on Intuitionistic Fuzzy Sets for Selection Among Third-Party Logistics Providers - Bali, Ozkan; Gumus, Serkan; Kaya, Ihsan (OLD CITY PUBLISHING INC, 2015)
Since the beginning of the 21st century, outsourcing has become an important strategic decision for firms that want to turn to their core competencies, to reduce logistics costs and to increase customer satisfaction. Owing to fact that outsourcing generally is encountered at logistics activities, third party logistics (TPL) providers play an important role in the success of the supply chain and the firm. For this reason, TPL provider selection has become a strategic decision making problem for firms and supply chain. Therefore, in this paper, a decision making procedure is presented for selection among third-party logistics providers based on intuitionistic fuzzy sets (IFSs) that is a stronger way than fuzzy set theory to express the uncertainty. Furthermore, a group dynamic intuitionistic fuzzy technique for order preference by similarity to ideal solution (DIF-TOPSIS) method is proposed for selecting the most appropriate TPL provider under uncertainty and in different time periods. This method is developed to enable the evaluation of the alternatives in different periods and its steps are presented for the application of a TPL provider selection problem. The proposed method is applied to a selection problem of two cargo companies for a firm which produces electrical radiator and wants to sale its products on the internet.
Keywords: Decision making; dynamic multi criteria decision making; intuitionistic fuzzy set; TPL provider selection; SUPPLIER SELECTION; MODEL; METHODOLOGY; Computer Science; Science & Technology - Other Topics